impact of lifestyle factors on serum 25-hydroxyvitamin D levels: a cross-sectional study in Japanese women aged 19-25 years - Ohta, Hiroaki; Kuroda, Tatsuhiko; Onoe, Yoshiko; Orito, Seiya; Ohara, Mami; Kume, Miyoko; Harada, Akiko; Tsugawa, Naoko; Okano, Toshio; Sasaki, Satoshi (Journal of bone and mineral metabolism, 2009)
Insufficient levels of serum 25-hydroxyvitamin D [25(OH)D] lead to low bone mineral density (BMD) by increasing serum levels of intact parathyroid hormone (PTH), and are associated with a high mortality rate. Therefore, the 25(OH)D level is used as an indicator of frailty in older persons. To obtain higher serum 25(OH)D levels, management of lifestyle habits and nutrient intake is important beginning in a person's younger years. This study evaluated the degree of association between serum 25(OH)D concentrations and lifestyle factors in young Japanese women. A cohort study was conducted from December 2003, and the survey was finished by February 2004. The subjects were 274 Japanese women aged 19-25 years old. The parameters evaluated in these subjects included: (1) serum concentrations of 25(OH)D, intact PTH, calcium, and phosphorus; (2) BMD in the lumbar spine and hip; and (3) lifestyle factors (nutrient intake, physical activity, and duration of sunlight exposure). The serum 25(OH)D level was negatively associated with the intact PTH level (Spearman; r = -0.17, P = 0.006). The BMD was significantly higher in the high 25(OH)D and low intact PTH group than the other group (P < 0.05). The serum 25(OH)D level was significantly correlated with daily intake of dietary vitamin D (r = 0.20, P = 0.001), the mean number of steps taken per day (r = 0.16, P = 0.010) and the mean time spent in sedentary activity (r = -0.14, P = 0.018) among the lifestyle factors evaluated. Multiple regression analysis showed the degree of association between lifestyle factors and serum 25(OH)D to be small (R ² = 0.084). Daily intake of dietary vitamin D and daily walking may be useful for increasing the serum 25(OH)D level in young Japanese women.